PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT BAGOES GLOBAL JAKARTA PUSAT - Pribadi Oviana, Anggun; Irawati, Laila (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence leadership style and work motivation have on employee performance at PT Bagoes Global Central Jakarta, both partially and simultaneously. This type of research uses descriptive quantitative research methods. The sampling technique used a saturated sample of 65 respondents, and data was collected through a questionnaire distributed via Google Form. Data analysis techniques use simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The research results show that: (1) Partially there is a significant influence between leadership style on employee performance at PT Bagoes Global Central Jakarta. This can be proven from the simple linear regression equation Y = 20.301 + 0.789 x1, the correlation value is 0.767. The coefficient of determination value is 76.7%, and the t value is 5.334 > t table 1.998 with a significance of 0.000 < 0.05. (2) Partially there is a significant influence between work motivation on employee performance at PT Bagoes Global Central Jakarta, this can be proven from the simple linear regression equation Y = 14.029 + 0.884 x2. The correlation value is 0.669. The coefficient of determination value is 66.1%, and the t value is 2.346 > t table 1.998 with a significance of 0.000 < 0.05. (3) Simultaneously there is a significant influence between leadership style and work motivation on employee performance at PT Bagoes Global Central Jakarta, this can be proven from the multiple linear regression equation Y= 13.114 + 0.602 (x1) + 0.340 (x2). The coefficient of determination value is 62.1%. And the Fcount value is 50.894 > Ftable 3.15 with a significance level of 0.000 < 0.05.